Correlating the Characteristics and Catalytic Performance of Mn-Na-W-Ox/SiO2 for Oxidative Coupling of Methane - Hamid Reza Godini; Stefan Berendts; Rafael Kleba-Ehrhardt; Asma Tufail Shah; Oliver Görke (Inorganics)
Chemical–structural characteristics of three differently synthesized research-benchmark Mn-Na-W-Ox/SiO2 catalysts for the Oxidative Coupling of Methane (OCM) were systematically studied in this research. XRD, EDX, ICP-OES, and SEM/FIB-SEM techniques, as well as Carrier Gas Hot Extraction (CGHE) and high-temperature XRD analyses, were performed to explain the functional features of the studied catalysts, in particular, the features affecting the quantity and quality of the interactions of oxygen and methane with the catalyst surface and with other molecular and radical species. These enable tracking the potential for the oxygen activation and dynamic transformation of the solid-state chemistry on the surface and sub-surface of these Mn-Na-W-Ox/SiO2 catalysts. These catalysts were synthesized, respectively, via the sol–gel synthesis method (Cat1) and the incipient wetness impregnation of the non-structured silica support (Cat2) and structured SBA-15 silica support (Cat3), under different sets of temperatures and gas compositions. The catalysts with the homogenous distribution of active components, namely Cat1 and Cat3, showed similar trends in terms of their dynamic interaction with oxygen species. They also showed higher levels of crystallinity of the active materials and higher catalytic selectivity towards ethane and ethylene. An explanation is given as to how the structural characteristics of the catalysts on the nanometer–micrometer scale contribute to these. The gained knowledge will be crucial in the selection and treatment of the support and developing a proper synthesis approach for the ultimate goal of designing a selective OCM catalyst.